Comparison of problem-based and team-based learning strategies: a multi-institutional investigation - Koriťáková, Eva; Jivram, Trupti; Gîlcă-Blanariu, Georgiana-Emmanuela; Churová, Vendula; Poulton, Ella; Ciureanu, Adrian Ioan; Louis, Chandran; Ștefănescu, Gabriela; Schwarz, Daniel (Frontiers in Education, 2023)
Objectives Over time, pedagogical practices in higher education have evolved significantly, which has led to the development of collaborative learning strategies. The study aims to compare the two most prominent ones – problem-based learning (PBL) and team-based learning (TBL). The comparison, integrated with Virtual Scenarios (VSs), involves student cohorts from various European institutions, specifically focusing on both PBL and TBL methods. The study is distinctive in its use of a consistent PBL/TBL methodology, ensured via joint staff training, and explores the perspectives of students and educators on these learning techniques. The overarching aim is to examine how PBL and TBL, coupled with VSs, influence problem-solving skills, independent learning, and student engagement. Methods The examination was made using feedback from 399 students and 11 tutors collected in four trials held in three institutions based in Czechia, the United Kingdom and Romania. The data gathered from surveys and a focus group discussion contained qualitative as well as quantitative data, such as Likert scale questions. To analyse the overall trends in learners’ satisfaction with PBL and TBL sessions, the mean score calculated from the transformed Likert scale questions was compared between sessions and among institutions using multivariate ANOVA. Results The students’ satisfaction and learning experience are heavily influenced by specific conditions, primarily their prior experience, room and technical set-up, group composition and especially the personality of a tutor. Overall, both strategies were found to be well-received by students used to traditional teaching methods. Students accustomed to PBL did not find TBL more engaging or useful. The identified advantages of TBL over PBL were the presence of a content expert, readiness tests, acquiring the same knowledge ensured through the collective presence of all students in one session and unified pre-class materials. However, TBL is more demanding on room set-up and teaching staff coordination. Conclusion Both strategies have been found to have pros and cons and neither showed clear superiority over the other one. An institution newly implementing PBL or TBL needs to focus on different aspects than an institution planning to switch from PBL to TBL.